IMPROVING PROFESSIONAL TRAINING OF FUTURE TEACHERS AS AN EDITORIAL PROBLEM - Mambetniyazov , Maksetbay Torebekovich (Innovative Development in Educational Activities, 2023)
In the article, as an editorial problem of improving the professional training of future teachers, the method of teaching information and communication technologies of teachers in the higher education system, the issue of organizing a lesson using Web-technologies and thereby forming their qualifications and skills It was said that the study of this problem is one of the urgent issues of insufficient research, in particular, the lack of skills and competences in the use and application of Web-technologies in the course of the lesson.